Detailed analysis of the association between urate deposition and bone erosion in gout: a dual-energy computed tomography study - Zheng, Wan-Yi; Zhan, Wen-Feng; Wang, Jing-Yi; Deng, Wei-Ming; Hung, Yu-Kai; Wang, Wei; Jiang, Gui-Hua (Frontiers in Endocrinology, 2023)
Objective: This study aimed to analyze the effect of urate deposition (UD) on bone erosion and examine the association between the volume of monosodium urate (MSU) crystals and an improved bone erosion score method, as measured in the metatarsophalangeal (MTP) joints of patients with gout. Materials and methods: Fifty-six patients diagnosed with gout using the 2015 European League Against Rheumatism and American College of Rheumatology criteria were consecutively enrolled. MSU crystals volume at each MTP joint was measured using dual-energy computed tomography (DECT) images. The degree of bone erosion was assessed with the modified Sharp/van der Heijde (SvdH) erosion scoring system based on CT images. Differences in clinical features between patients with (UD group) and without (non-UD group) UD were assessed, and the correlation between erosion scores and urate crystal volume was analyzed. Results: The UD and non-UD groups comprised 30 and 26 patients, respectively. Among the 560 MTP joints assessed, 80 showed MSU crystal deposition, and 108 showed bone erosion. Bone erosion occurred in both groups but was significantly less severe in the non-UD group (p <0.001). Both groups had equivalent levels of serum uric acid (p=0.200). Symptom duration was significantly longer in the UD group (p=0.009). The UD group also had a higher rate of kidney stones (p=0.023). The volume of MSU crystals was strongly and positively associated with the degree of bone erosion (r=0.714, p <0.001). Conclusions: This study found that patients with gout and UD show significant increased bone erosion than those without UD. The volume of MSU crystals is associated with the improved SvdH erosion score based on CT images, regardless of serum uric acid level, demonstrating the potential of combining DECT and serum uric acid measurements in helping optimize the management of patients with gout.